The difficulty of predicting clinical outcome after intended submaximal resection of large vestibular Schwannomas. (April 2018) - MacKenzie, Rebecca; Sporns, Peter; Zoubi, Tarek; Koopmann, Mario; Ewelt, Christian; Stummer, Walter; Brokinkel, Benjamin; Suero Molina, Eric
Highlights: A large collective of patients harboring large vestibular schwannomas is analyzed. They are classified according to the Hannover classification 4a and 4b. All patients included underwent intended submaximal resection. These are some highlights from this manuscript: It is demonstrated that submaximal resection provides a favorable neurological outcome. This is especially true for patients with large VS. Risk factors are analyzed in a large collective. It is difficult to predict postoperative neurological outcome based on risk factors. Only 24% of patients demonstrated a deterioration of facial nerve function. Deterioration was classified as serviceable to non-serviceable level. Hearing function deteriorated from a serviceable to a non-serviceable level in 21%. Deterioration of facial nerve function increased with preoperative tumor volume. Hearing more often worsened with previous microsurgery or radiosurgical treatment. Abstract: Introduction: Intended subtotal resection of large vestibular schwannomas (T4a and b according to the Hannover classification system) has been shown to be safe and, in combination with stereotactic radiosurgery, might enable sufficient tumor control. However, risk factors for postoperative neurological deterioration in these surgically challenging lesions are largely unknown. Methods: Pre- and postoperative symptoms, clinical and radiological data of patients who underwent intended subtotal resection for vestibular schwannoma in our department between 2010 and 2014 were reviewed. Risk factors for postoperative neurological deterioration were analyzed in uni- and multivariate analyses. Results: 63 patients harboring T4a (N = 33, 52%) or T4b (N = 30, 48%) tumors were included. At time of discharge, facial nerve and hearing function had deteriorated from a serviceable to a non-serviceable level (H&B grades I + II vs. >II) in 24% (N = 15/63) and 21% (N = 6/29), respectively. Deterioration of vertigo was more common after near (N = 3/9, 33% vs. 2/38, 5%) than after subtotal resection (<.25 ccm vs. ≥ .25 ccm tumor remnant on the initial postoperative MRI; p = .042). No further correlation with patient age, sex, neurofibromatosis, resection extent and tumor volume, or -cyst volume was found. Patients were reevaluated after a median of 3 months after surgery. At that time, facial nerve function and hearing had both decreased from a preoperative serviceable to a non-serviceable level in 5%. In univariate analyses, risk of deterioration of facial nerve function increased with preoperative tumor volume (p = .037). Conclusion: Intended submaximal resection provides satisfactory neurological outcome for patients with large VS. Risk factors for postoperative neurological deterioration remain unclear.